Questioning Fe isotopes as a provenance tool: Insights from bog iron ores and alternative applications in archeometry. (January 2019) - Rose, Thomas; Télouk, Philippe; Klein, Sabine; Marschall, Horst R.
Abstract: Provenancing metal artifacts with scientific methods is an established tool in archeometry to identify the metal deposits, which were exploited for the production of ancient metal objects. It is thus an important method to reconstruct ancient exchange networks and the socio-economic organization of past societies. Previously introduced isotope-based approaches (Pb, Sr, Os) and chemical analyses of slag inclusions have severe limitations concerning their application or the amount of sample required. Fe isotopes were previously suggested in a quite early stage of investigation as a potential provenance tracer and it was postulated that they would not fractionate during the smelting procedure. However, previously published analytical data from iron ores indicate a wide overlap between deposits. Further, the earlier studies on Fe isotopes did not included bog iron ores, despite their high importance in ancient metallurgy. As geochemical reactions during ore formation are complex and fractionation cannot be generally excluded, the applicability of Fe isotopes as an alternative provenance tracer still asks for further investigation. This purely methodological study focuses on specimens from two sites of the formerly mined bog iron ore deposit Eyller Bruch (Germany), which are analyzed together with products of a smelting experiment based on these ores. The Fe isotopic composition of the bog iron ore from the investigated region suggests an intra-deposit zonation caused by environmental parameters and its overall variation is comparable with that of other deposits. The bog iron ore isotope signature largely overlaps with the isotope range of mineralizations in other regions. As a consequence of this and although the absence of Fe isotope fractionation during the smelting procedure is confirmed, the study demonstrates the lack of discriminatory power of Fe isotopes for provenance studies. Potential applications for archeometry can rather be found in the environmental parameters, especially organic matter, which seems to have a strong influence on Fe isotope compositions of bog iron ores. Zonations within deposits might be identified and could help to reconstruct the exploitation history of the deposit or to reconstruct past bog landscapes. Highlights: Iron isotopes for ancient iron metal tracing revisited. Bog ores from one deposit substantially overlap with nearly all other ore types. Iron isotopes lack for discriminatory power for provenance studies. Bog ores in a single deposit might be differentiated according to their host soil.